Digital identification of the emission spectrum lines of magnetron discharge - Afanasіeva, I.A.; Afanasiev, S.N.; Bobkov, V.V.; Gritsyna, V.V.; Drozdov, D.R.; Logachev, Yu.E.; Skrypnyk, A.A.; Shevchenko, D.I. (Вопросы атомной науки и техники, 2019)
To obtain the qualitative and quantitative characteristics of the discharge plasma spectrum in the Python programming language, a multifunctional interactive GUI-application OSA (Optical Spectrum Analyzed) was created. The application allows you to download a digital image of the optical spectrum, automatically determine the wavelength of the selected spectral line and do elements interpretation. Для отримання якісних і кількісних характеристик спектра плазми розряду на мові програмування Python створено багатофункціональний діалоговий GUI-додаток OSA (Optical Spectrum Analyzed). Додаток дозволяє завантажити цифрове зображення оптичного спектра, в автоматичному режимі визначити довжину хвилі обраної спектральної лінії і виконати елементну інтерпретацію. Для получения качественных и количественных характеристик спектра плазмы разряда на языке программирования Python создано многофункциональное диалоговое GUI-приложение OSA (Optical Spectrum Analyzed). Приложение позволяет загрузить цифровое изображение оптического спектра, в автоматическом режиме определить длину волны выбранной спектральной линии и выполнить элементную интерпретацию.